Formulation And Physical Properties Evaluation Of Beach Morning Glory (Ipomoea Pescaprae) Leaves Ointment - Meddo Lorenza Garnida; Delladari Mayefis; Habibie Deswilyaz; Arie Vonikartika; Mega Sari, Diani (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2023)
Background: Sea kangkung is one of the plants used as traditional medicine which is widely used as a topical medicine, one of which is to treat jellyfish stings and ulcers. This study aims to determine how to formulate ointment preparations from sea kangkung extract and to test the physical properties of sea kangkung preparations. Methods: Sea kangkung leaves were extracted using the maceration method using methanol as a solvent and then made preparations in the form of an ointment using concentration variations, namely (F1) - , (F2) 1 % , (F3), 3 % (F4), 5 % (F5) 10 %. Furthermore, the physical stability test of the ointment was carried out, namely the Cycling Test including organoleptic test, homogeneity test, pH test and spreadability. Results: The results obtained that sea kangkung extract ointment has a fairly good stability based on the stability test of the third formula, which is the most stable preparation.